Barbarian's hope - Dixon, Ruby, 1976- (Ice planet barbarians, 2025)
"The next novel in the Ice Planet Barbarians series, an international publishing phenomenon-now in a special print edition with bonus material! Asha and Hemalo's relationship has never been easy, for as much love is between them, there is as much hurt. Will they find their way back to each other, or will they let tragedy keep them separated for good? Seasons ago, I resonated to the quietest of tribesmates, a male content to love me from afar while I was the center of attention. We could have been happy. Despite our differences, I loved him and he loved me. But then a terrible thing happened...and my world was never the same again. Now resonance is giving us a second chance, but...I'm afraid. What if what I have with my mate is too broken to be fixed? What if there's no hope left for us at all?"--